Study onthe Preparation and Performance of Novel Waterborne Epoxy Zinc-Rich Coating - CAO Qian, CHENG Xu-dong, LIU Wei, LIU Rui-qing, XU Kai, YU Fei (Cailiao Baohu, 2021)
In order to meet the requirement of durability in the field of heavy anti-corrosion coating, a waterborne epoxy zinc-rich primer with strong corrosion resistance and high storage stability was prepared by adjusting the proportion of zinc powder in the epoxy zinc-rich coating, adding silane coupling agent and optimizing the coating anti-settling system.The effects of the three components of zinc powder, coupling agent and anti-settling agent on the corrosion resistance, adhesion to the substrate and storage stability were studied systematically.In addition, the prepared coating was combined with epoxy intermediate coating and waterborne polyurethane to constitute a complex coating system, and their neutral salt spray(NSS)corrosion resistance and adhesion of the system were analyzed.Results showed that during the preparation process of epoxy zinc-rich primer, controlling the content of organic bentonite and lipophilic fumed silica could improve the storage stability of the coating.When the amount of zinc powder was 55%(mass fraction, the same below), the contents of anti-settling agent, organic bentonite and fumed silica are 0.8% and 1.0% respectively, the storage stability of the as-obtained coating could reach grade 10; when the content of silane coupling agent was 1.5%, the bonding strength between the coating and the substrate could reach 11.3 MPa.The coating could act as primer then form a composite coating system with epoxy intermediate coating and water-based polyurethane top-coating, which withstood 3 600 h NSS corrosion test without peeling, inducing that the coating system could be promisingly used in the field of heavy corrosion protection.